Clinical presentation of atrial myxoma does it differ in left or right sided tumor? - Khan, Habib; Chaubey, Sanjay; Uzzaman, Mohammed Mohsin; Iqbal, Yasir; Khan, Fareeda; Butt, Salman; Deshpande, Ranjit; Desai, Jatin (International Journal of Health Sciences, 2018)
Objective: This paper reports a twenty year experience of the management of atrial myxomas at our institution. Apart from presenting our experience of their clinical presentation, surgical management, post-operative complication and long term follow up we investigated any correlation between left and right sided tumor with their symptom of presentation. Methods: The data was retrospectively collected for patients between the period 1995 to 2015 from the hospital database. The follow up was conducted by questionnaire received from the patients describing their current status. Results: Fifty four consecutive patients underwent surgical resection for atrial myxomas. The mean age was 62years (SD: ±14years) with a larger number of female (55.5%) patients. The most common location for the tumour was the left atrium (70.3%) with the atrial septum being the most common (63%) site of attachment. The tumors presented in a variety of ways namely as shortness of breath (37.03%), transient ischemic attack (24.07%) and chest pains (22.2%) being the more common modes of presentation. Left heart tumors presented six years earlier with more severe shortness of breath as compared to right sided tumours. Post-operative atrial fibrillation occurred in 22.2% of patients. Concomitant surgical procedures were required in 26% of patient. The median length of postoperative hospital stay was 6 days (IQR: 5;9). There were 2 (3.7%) in-hospital mortalities and 4 (7.4%) later deaths at 2, 3, 7 and 15 years respectively. Long term follow-up actuarial Kaplan-Meir survival for the whole group was 92.6% +/- 3.6 % at 20 years with a significant reduction in the severity of shortness of breath. Conclusion: Cardiac myxoma is the most common form of cardiac tumor with a slight female preponderance. Left sided tumors present earlier than right sided tumors with more severe shortness of breath. Excellent long term results can be achieved with surgical intervention for cardiac myxomas, including any concomitant interventions. In particular a sustained reduction in shortness of breath is observed.